AN ANALYSIS OF TYPES OF DEIXIS IN THE SONG LYRICS OF 'GIVE ME YOUR FOREVER' BY ZACK TABUDLO - Mustafidah, Any Dinda Zahrotul; Putri, Aprilia Riyana (University of Kuningan, 2025)
This study aims to analyze the deixis used in the lyrics of the song